Financial Development and Innovation in Small Firms - Sharma, Siddharth (World Bank, Washington, DC, 2012)
This paper uses firm level data from a cross-section of 57 countries to study how financial development affects innovation in small firms. The analysis finds that relative to large firms in the same industry, spending on research and development by small firms is more likely and sizable in countries at higher levels of financial development. The estimates imply that among firms doing research and development in a country like Romania, which is at the 20th percentile of financial development, a 1 standard deviation decrease in firm size is associated with a decrease of 0.7 standard deviations in research and development spending. In contrast, this decrease is only 0.2 standard deviations in a country like South Africa, which is at the 80th percentile of the distribution of financial development. Small firms also report producing more innovations per unit of research and development spending than large firms, and this gap is narrower in countries at higher levels of financial development. As a robustness check, the author shows that these patterns are stronger in industries inherently more reliant on external finance.